STUDI EKSPERIMEN GELOMBANG PADA BEBERAPA MEDIA EXPERIMENTAL STUDY OF WAVES ON SEVERAL MEDIA - Dea Rafika Syahputri; Melynda Sari (JOURNAL SAINS STUDENT RESEARCH, 2025)
Waves are movements that pass through something or space. They carry energy that affects other energies. This study uses experimental methods, which means it is based on experimental research. The aim of this research is to observe the shape and type of transverse waves and longitudinal waves, as well as determine the nature of wave reflection. This research uses an experimental method, which means it is based on experiments. Researchers collect information by observing and recording what is done and seen. T This research was conducted at STKIP Al Maksum Langkat. The results of this experiment show that the length of what the wave is traveling through, whether it's a slinky or a hemp rope, affects how many waves are produced and how long it takes to propagate. Additionally, you can see how the waves bounce back, which is a basic feature of waves.